Mutacje mitochondrialnego DNA w chorobach narządu wzroku – dziedziczna neuropatia nerwu wzrokowego Lebera oraz zespół Kearnsa - Rydzanicz, Małgorzata; Mrugacz, Małgorzata; Gajęcka, Marzena (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Mitochondrial diseases are caused by mitochondrial structure aberrations and function deficiency. The clinical heterogeneity of mitochondrial diseases is associated with the type of causing mutations (de novo or maternally transmitted mutations), and several aspects of mitochondrial genetics and inheritance, including heteroplasmy. In this paper, we explain the basics of mitochondrial genetics and inheritance as well as genetic background of mitochondrial related disorders: Leber’s hereditary optic neuropathy and Kearns’ syndrome.